A Case Report of Gastrointestinal Hemorrhage and Perforation During Apatinib Treatment of Gastric Cancer. Issue 39 (September 2015) - Li, Xiao-Fen; Tan, Yi-Nuo; Cao, Ying; Xu, Jing-Hong; Zheng, Shu; Yuan, Ying; Kumar., Raj
<x xml:space="preserve">Abstract</x> Abstract Apatinib is a novel tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2, which shows good efficacy and safety in clinical trials for chemotherapy-refractory gastric cancer patients. Till now, there is no case report after apatinib came in the market. We presented a 55-year-old Chinese woman with advanced gastric cancer, who received apatinib after failure of second-line chemotherapy. On the 19th day of apatinib administration, she suffered from gastrointestinal hemorrhage. Then, her condition rapidly deteriorated to gastrointestinal perforation. Although the patient received timely medical and surgical treatment, she finally died of septic shock. Although apatinib shows exciting efficacy and good tolerance in phase II and III clinical trials, this novel targeted drug should be prescribed carefully and close clinical monitoring is needed when using it.